Analisis Perilaku Konsumen dalam Pembelian Barang Online: Literatur Review - Putri Ayu (Ekonomis: Journal of Economics and Business, 2023)
In traditional economic theory, decision making by individuals is taken rationally to maximize satisfaction, but in behaviora economic theory there are no assumptions such as rationality in decision making, namely how individuals directly behave in various situations. This study aims to review the literature that discusses how behavioral economics influences individuals to buy online shopping. The method used is literature review paper from indexed national and international journals. From the scheme used, 11 papers were reviewed. The results show that consumers' attitudes toward purchasing goods online are generally significantly influenced by psychological, cultural, social, and personality factors. However, there are also other factors that also influence consumer attitudes towards online product purchases, such as perceived benefits, perceived risks, website design, hedonic motivation, convenience, responsiveness, trustworthiness, security, quality issues, promotions, products, prices. , time efficiency, and a wide variety of goods. However, there are several journals that show an insignificant relationship between economic behavior and its decisions.